Critical Review of the Proposed Model for Productive Zakat Distribution - Hartato Rianto (International Journal of Economic, Technology and Social Sciences (Injects), 2025)
This study explores a model of productive zakat distribution in Indonesia, with particular emphasis on oversight and effectiveness. The model highlights a collaborative framework between Zakat Management Organizations (OPZ) and Islamic banks, in which zakat funds are utilized as collateral to help non-bankable mustahiq access business capital. The approach aims to empower mustahiq toward economic self-reliance, with the long-term vision of transforming them into future muzakki (zakat payers). However, the study identifies several critical shortcomings, including the absence of clearly defined selection criteria for mustahiq, inadequate supervision across the various stages of zakat distribution, and inefficiencies in fund allocation—particularly the use of zakat to cover insurance premiums. In response, the research offers targeted recommendations: strengthening monitoring mechanisms, enhancing the entrepreneurial capacity of mustahiq, and optimizing the allocation of productive zakat funds to maximize economic impact. This study aspires to serve as a valuable reference for OPZ and other stakeholders in the development of zakat distribution models that are more efficient, transparent, and genuinely focused on sustainable economic empowerment for mustahiq